Psychological Contracts and Employee Innovative Behaviours: A Moderated Mediation Effect Model - Huihui Li; Congwei Xu; Huizhen Zheng (Discrete Dynamics in Nature and Society)
According to Bakker and Demerouti’s work demand resource theory, abundant work resources can stimulate an individual’s initiative to the maximum extent and finally achieve ideal work results. However, few scholars have discussed if psychological states could affect work resources. We believe that relationship embeddedness is an important work resource in the context of Chinese human relationship culture. A low degree of embeddedness among employees would affect employees’ recognition of their organizations and reduce their motivation for voluntary innovative behaviours. This study was to provide empirical evidence on the relationship between psychological contracts and employee innovative behaviours as well as the mediating role and moderating role of relational embeddedness and organizational tenure. A descriptive cross-sectional survey design was adopted. Primary data were collected by a structured questionnaire targeting the employees in China. To test the hypotheses, data collected from 402 enterprise employees were used for a regression analysis in AMOS (version 22). We found that there is a significant positive correlation between psychological contract and employee innovation behaviour, while embedding strength and embedding quality mediated the influence of psychological contracts on employee innovative behaviours. Organizational tenure moderated the strength of the relationship between psychological contracts and employee innovative behaviours via embedding strength and embedding quality.